The role of individual and community empowerment as drivers of contraceptive use among reproductive aged women in Bangladesh: Insights from multilevel analysis using BDHS 2022 - Bikash Pal; Md. Abdus Salam Akanda (PLoS ONE, 2026)
This study explores the impact of individual and community-level women’s empowerment on contraceptive use in Bangladesh, a country where disparities in access and utilization of modern family planning services persist. Drawing on socio-ecological theory, the research examines how both personal agency and the broader social environment interact to influence women’s reproductive health decisions. Mann–Whitney U tests and chi-square tests were used for unadjusted comparisons, followed by multilevel logistic regression to account for clustering at the community level. Using data from the 2022 Bangladesh Demographic and Health Survey (BDHS), the study finds that community-level empowerment was significantly and positively associated with contraceptive use, whereas individual empowerment showed a positive but marginal association (p-value ≈ 0.10). However, community empowerment appears to have a stronger and more consistent effect than individual empowerment. Key socio-economic factors, such as age, education, and residence also significantly influence contraceptive use. The findings underscore the role of community-level empowerment in shaping women’s reproductive health decisions. Community-based strategies, such as women’s support groups, health volunteers, and local leadership engagement, may offer more sustainable improvements in contraceptive use than individual-focused approaches. This study adds to the growing evidence base on empowerment and reproductive health, and provides actionable program design in similar sociocultural contexts.